Forced Molting: A Technique to Improve The Egg Production of Duck in The Next Laying Cycle - Setioko, Argono Rio (Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Molting is a physiological process that involves the shedding of old feathers and the growth of the new one in birds. It is affected by hormonal, where the ovary regresses and the egg production automatically ceases. Although molting is a natural phenomena, this can be induced artificially that commonly called "forced molting" by manipulating the environment such as feed, water, light or chemical compounds. This method is aimed to shed the feathers spontaneously and stop the egg production. After having a rest from laying, the birds start laying again at the same time and hopefully have a better egg production. Beside increasing egg production, forced molting could also extend the laying period up to the certain economical level. This paper describes the term of molting, process of molting and techniques of forced molting technique. Key words: Molting, forced molting, duck, egg